Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T15:25:41+01:00
Niech
α = I ∢ CAB I
β = I ∢CBA I
γ = I ∢C1CC2 I
I ∢ ACC1 I = [180⁰ - α] /2, bo Δ ACC1 jest równoramienny, gdyż
I AC I = AC1 I
I ∢ BCC2 I = [180⁰ - β] /2 , bo Δ BCC2 jest równoramienny, gdyż
I BC I = I BC2 I
∢ ACB jest prosty, zatem I ∢ ACB I = 90⁰
[180⁰ - α]/2 + [180⁰ - β] /2 = 90⁰ + γ
zatem
[360⁰ - (α + β)]/2 = 180⁰ - [α + β]/2 = 90⁰ + γ
γ = 180⁰ - 90⁰ -[α + β]/2 = 90⁰ - [α +β]/2 = 90⁰ - 90⁰/2 =
= 90⁰ - 45⁰ = 45⁰
gdyż α + β = 90⁰/
Odp. γ = I ∢ C1 C C2 I = 45⁰.
5 4 5